Th17 Cells Paradoxical Roles in Melanoma and Potential Application in Immunotherapy - Chen, Chen; Gao, Feng-Hou (Frontiers in Immunology, 2019)
Progressively infiltrating of immune cells are associated with the progression of melanoma. Especially, Th17 cells in melanoma microenvironment have both antitumor and protumor effects. It is necessary to understand the contradictory data of how Th17 cells play a role in melanoma. This review will summarize the current knowledge regarding the potential mechanisms that may be involved in the effects of Th17 cells in melanoma progression. Currently, since adoptive transferring Th17 cells has made great success in eradicating melanoma in mice, it becomes the primary strategy that the enriching stemness-like memory Th17 cells by adding distinct cytokines or pharmacologic reagents augment Th17 cells expansion ex vivo and enhance antitumor effect in next-generation trials and its clinical implications.